2009
DOI: 10.1387/ijdb.082840dc
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of the intersex homologous gene in the pest lepidopteron Maruca vitrata

Abstract: The intersex (ix) gene works in concert with doublesex (dsx) at the bottom of the sexdetermination hierarchy to control somatic sexual differentiation in Drosophila melanogaster females. Here we report the isolation and characterization of the Drosophila intersex (ix) homologue in the pest lepidopteron Maruca vitrata (Mvix). The Mvix gene exhibits major complexity with respect to the Drosophila homolog. It is expressed in males and females and its pre-mRNA is subject to differential splicing events which affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…The present study provides evidence for the presence of an alternative splice form of ix in three species of silkmoths examined. Taken together with the results of an earlier study on ix in piralid moth, Maruca vitrata (Cavaliere et al 2009), the present study suggests that the testis-specific splice form may be a characteristic feature of lepidopterans. Though ix lacks a conserved splicing pattern it appears to have retained its functional conservation in terminal sexual differentiation.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The present study provides evidence for the presence of an alternative splice form of ix in three species of silkmoths examined. Taken together with the results of an earlier study on ix in piralid moth, Maruca vitrata (Cavaliere et al 2009), the present study suggests that the testis-specific splice form may be a characteristic feature of lepidopterans. Though ix lacks a conserved splicing pattern it appears to have retained its functional conservation in terminal sexual differentiation.…”
supporting
confidence: 87%
“…Much of the work on functional aspect of ix has been done in Drosophila, whereas among lepidopterans, ix has been reported in B. mori and the piralid agricultural pest, Maruca vitrata. In M. vitrata, a female-specific ix transcript is found only in pupae, which appears to be the first described sexspecific transcript of an ix homologue characterized to date (Cavaliere et al 2009). In another study, a B. mori homologue of ix (Bmix) was identified using Expressed Sequence Tags (ESTs) resources, and it was found that ix-mutant Drosophila females expressing Bmix cDNA restored partial characteristics of the wild type phenotype (Siegal and Baker 2005).…”
Section: Introductionmentioning
confidence: 82%
“…In Drosophila, intersex, a gene implicated in female sexual development is expressed in both the sexes and functions together with doublesex (dsx) to regulate terminal sex differentiation in females. Recent studies on Ix proteins isolated from Maruca vitrata (Cavaliere et al 2009) and B. mori (Arunkumar and Nagaraju manuscript communicated) and their partial rescue of Drosophila ix mutant (Cavaliere et al 2009;Siegal and Baker 2005) suggest that it may be functionally conserved to exhibit its role in sex differentiation in co-ordination with Dsx. In light of this, finding of a novel female-specific splice form of dsx in lepidopterans, which codes for another female-specific putative protein, opens up a new avenue to unravel the sexual differentiation process governed by BmDsx proteins in the lepidopterans.…”
Section: Discussionmentioning
confidence: 99%
“…Among lepidopterans, ix homologs have been reported to be present in domesticated and wild silkmoths, including B. mori , A. assama , A. mylitta , and Samia cynthia ricini [Siegal and Baker, 2005;Arunkumar and Nagaraju, 2011]. Besides silkmoths, ix has also been characterized in Maruca vitrata , a Piralidae moth [Cavaliere et al, 2009]. Unlike Drosophila , ix in B. mori , A. assama , and M. vitrata produces sex-specific alternatively spliced isoforms [Cavaliere et al, 2009;Arunkumar and Nagaraju, 2011].…”
Section: Intersex and Fruitlessmentioning
confidence: 99%
“…Besides silkmoths, ix has also been characterized in Maruca vitrata , a Piralidae moth [Cavaliere et al, 2009]. Unlike Drosophila , ix in B. mori , A. assama , and M. vitrata produces sex-specific alternatively spliced isoforms [Cavaliere et al, 2009;Arunkumar and Nagaraju, 2011]. Functional significance of the different IX isoforms in lepidopteran sex determination has yet to be investigated.…”
Section: Intersex and Fruitlessmentioning
confidence: 99%